2014
DOI: 10.3390/ma7032370
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of the Uniaxial-Strained nMOSFET with a Fluorinated HfO2/SiON Gate Stack

Abstract: The channel fluorine implantation (CFI) process was integrated with the Si3N4 contact etch stop layer (SiN CESL) uniaxial-strained n-channel metal-oxide-semiconductor field-effect transistor (nMOSFET) with the hafnium oxide/silicon oxynitride (HfO2/SiON) gate stack. The SiN CESL process clearly improves basic electrical performance, due to induced uniaxial tensile strain within the channel. However, further integrating of the CFI process with the SiN CESL-strained nMOSFET exhibits nearly identical transconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Alternatively, it was noteworthy that the largest MW value was obtained (12.0 V) for the A4 device. The synergic effects of CF 4 plasma and thermal annealing processes can be explained by following two feasible scenarios: (1) in terms of the Al:HfO 2 CTL bulk, two types of trap centers including the shallow trap sites located along the grain boundaries formed by crystallization and the deep trap sites within the midgap regions by incorporation of F ions could be generated by combined CTL engineering processes. In other words, residual F ions at the Al:HfO 2 CTL surfaces could be diffused into the Al:HfO 2 bulks by postannealing treatment, inducing the deep trap sites due to the reactions with Hf dangling bonds. As a result, the charge-trapping efficiency could be quite improved by a significant increase in stable charge-trap sites; (2) in terms of the TL/CTL interfaces, the number of residual impurities and oxygen vacancies could be effectively reduced by combination of CF 4 plasma and annealing treatments, contributing to effective suppression of unstable charge-trapping events at interfaces.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, it was noteworthy that the largest MW value was obtained (12.0 V) for the A4 device. The synergic effects of CF 4 plasma and thermal annealing processes can be explained by following two feasible scenarios: (1) in terms of the Al:HfO 2 CTL bulk, two types of trap centers including the shallow trap sites located along the grain boundaries formed by crystallization and the deep trap sites within the midgap regions by incorporation of F ions could be generated by combined CTL engineering processes. In other words, residual F ions at the Al:HfO 2 CTL surfaces could be diffused into the Al:HfO 2 bulks by postannealing treatment, inducing the deep trap sites due to the reactions with Hf dangling bonds. As a result, the charge-trapping efficiency could be quite improved by a significant increase in stable charge-trap sites; (2) in terms of the TL/CTL interfaces, the number of residual impurities and oxygen vacancies could be effectively reduced by combination of CF 4 plasma and annealing treatments, contributing to effective suppression of unstable charge-trapping events at interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it could be verified that the CTM-TFT using the Al:HfO 2 CTL treated with P+T exhibited far superior NVM characteristics and operational reliabilities among the fabricated devices, which correspond to indirect evidence for the F diffusion during the thermal annealing process at 500 °C. Additionally, it was also reported that F ions diffuse into the HfO 2 bulks during the CF 4 plasma and postannealing treatments, generating deep trap sites within the HfO 2 bandgap. Therefore, from these viewpoints, it was reasonably suggested that the stable charge-trap sites can be generated by F incorporation into the bulk region of the Al:HfO 2 CTL. Alternatively, small degrees of modulations in numerical values of the bandgap with CTL engineering processes were supposed to have negligible effects on the NVM operations of the CTM-TFTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Titanium doping was found to suppress the oxygen vacancies in tantalum oxide capacitors, which resulted in a significant reduction in the leakage current [38]. For the HfO 2 capacitors, there are also a considerable number of oxygen vacancies [39,40,41,42], which could potentially be suppressed when titanium is doped in the HfO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, much effort has been devoted to exploring passivation methods for V O defects. The primary strategy is to use various anions such as nitrogen, oxygen and fluorine to coordinate with metal dangling bonds in MOSs [11]. The passivation process is conducted under high temperature or with the aid of plasma.…”
Section: Introductionmentioning
confidence: 99%